2001
DOI: 10.1023/a:1011237019082
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Anaphylactoid reactions in patients receiving intravenously administered vitamin K have been reported in the literature. To summarize the known data on anaphylactoid reactions from administration of vitamin K, we reviewed all published and unpublished reports of this adverse reaction. Published reports were obtained through medline (1966--1999) and EMBASE (1971--1999) searches of the English language literature and review of references from identified case reports. Unpublished reports were obtained using the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The consistent symptoms include facial flushing, vague uneasy feelings of weakness, abdominal and low back pain, nausea, vomiting, dyspnea, and chest pain. In severe reactions, these symptoms are followed within minutes by cyanosis, loss of consciousness, and hypotension, with the potential for cardio-pulmonary arrest and death [2], [3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The consistent symptoms include facial flushing, vague uneasy feelings of weakness, abdominal and low back pain, nausea, vomiting, dyspnea, and chest pain. In severe reactions, these symptoms are followed within minutes by cyanosis, loss of consciousness, and hypotension, with the potential for cardio-pulmonary arrest and death [2], [3].…”
Section: Introductionmentioning
confidence: 99%
“…The medical use instructions for VK 1 products from Merck, US, report that VK 1 can induce anaphylaxis. After reviewing the reaction description (CONSTART terms, “Coding symbols for a thesaurus of standard adverse reaction terms”) in the Food and Drug Administration SRSAR file, Louis found that the patients who experienced such a reaction were never identified as “anaphylactoid” [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of the reported anaphylaxis episodes occurred with older vitamin K formulations containing polyethoxylated castor oil, while the modern micelle formulation is thought to have a lower risk of anaphylactoid reactivity [33]. A 2001 review of anaphylactoid reactions associated with vitamin K reported 23 (3 fatal) case reports and 132 FDA-reported adverse drug events from IV vitamin K, 32 individuals following intramuscular administration, 13 patients following SQ vitamin K, and 7 individuals following oral vitamin K [34]. In conclusion, 5-10 mg of vitamin K should be given slowly by IV when a patient presents with WAICH.…”
Section: Resultsmentioning
confidence: 99%